Long-term administration of prolactin or testosterone induced similar precancerous prostate lesions in rats - Herrera-Covarrubias, D.; Coria-Avila, G.A.; Chavarra, X.P.; Fernndez-Pomares, C.; Manzo, J.; Aranda-Abreu, G.E.; Hernndez, M.E. (Experimental Oncology, 2015)
Evidence indicates that prolactin plays a crucial role in the normal function and development of the prostate, but abnormal high levels of the hormone are associated with hyperplasia and cancer of the gland. Aims: The present study was designed to describe the progressive specific histological abnormalities in the prostate of rats with chronic hyperprolactinemia. Material and Methods: Prolactin was administered during 4; 12 or 24 weeks, and the resulting prostatic alterations were compared with control rats, and also with those treated with testosterone, or the combination of prolactin + testosterone. Results: Rats treated with prolactin, testosterone or prolactin + testosterone expressed precancerous histological abnormalities in the dorsolateral and ventral portions of the prostate as early as in 4 weeks of treatment, but in all cases the malignancy increased after 12 or 24 weeks of treatment. Conclusion: Our study confirms that chronic hyperprolactinemia is a cause of prostate precancerous pathologies. Key Words: prolactin, prostate, cancer, dysplasia, testosterone.